A Review on Sick Building Syndrome (SBS) - Bello, Yusuf Samaila (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Sick building syndrome (SBS) constitutes a group of symptoms that occur in a building affecting occupants, but disappear mostly after leaving the building. Sometimes biological aspects cause SBS, sometimes the chemicals present in your building, but human biological systems are affected. This paper reveal a review of SBS, including symptoms, causes, effects, work-related illnesses, prevention, and control. Sick Building Syndrome (SBS) is a medical condition where people experience unexplained symptoms of illness or discomfort while occupying a building. The severity of these symptoms tends to worsen with prolonged stay in the building, but improves or disappears once they leave. SBS can have significant consequences, including: Impaired work or school performance, strained personal relationships, Reduced attendance, Decreased productivity. SBS can occur in various settings, such as: Offices, Homes, Schools, Nurseries. Common symptoms of SBS include: Eye problems (irritation, watering, dryness), Respiratory issues (runny or blocked nose, sore throat), Skin problems (itching, dryness), Headaches, Fatigue, Lethargy, Poor concentration. Overall, SBS can have a significant impact on an individual's quality of life and productivity, making it essential to identify and address the underlying causes of the condition.